Ocean-Atmosphere Interactions of Gases and Particles. - Liss, Peter S.; Johnson, Martin T. (Berlin, Heidelberg : Springer Berlin / Heidelberg, 2014)
This book examines how gases and particles formed in the oceans affect the chemistry and physics of the atmosphere when they move from ocean to atmosphere. It also details how material deposited from the atmosphere affects the biogeochemistry of the oceans.
5.2.1.2 Diagnostic Approaches: Based on Empirical Correlations.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books